A method for requirements elicitation of a data warehouse : an example - Sá, Jorge Vaz de Oliveira e (2014)
This paper presents a method with a combination of diverse approaches for requirement elicitation of a Data Warehouse (DW) schema model. This method integrates five approaches: goal-driven, user-driven, process driven, technology-driven, and data driven. This method includes two approaches not usually used in the DW field: process-driven and technology driven. The role of each approach is: goal-driven produces subjects (DW processes) and KPI’s (Key Performance Indicators) of main business fields; user-driven produces analytical requirements represented by measures and dimensions of each subject; process-driven propose improvements in business processes (by using and creating subject oriented enterprise data model) to satisfy KPI’s, measures and dimensions identified in the previous approaches; technology driven is an enabler or an obstacle to be considered in a DW; and data-driven is a combination of the results of previous approaches and results in a DW schema. By using a method with five approaches, a layered DW schema aligned with business and individual needs can be obtained. This will be illustrated by using examples.